2020
DOI: 10.1002/mde.3238
|View full text |Cite
|
Sign up to set email alerts
|

Competitors matter: How competitors' actions moderate the influence of firm profitability on the prioritization between growth and efficiency increase

Abstract: Firms have been shown to prioritize between growth and efficiency increase sequentially depending on their level of profitability. Adding arguments from the attention‐based view to this discussion, we hypothesize that actions of competitors in the marketplace could moderate this relationship. Using data from business simulations, we specifically test whether the influence of firm profitability on the prioritization decision varies with changes in competitor products' pricing, promotion, and quality. Our analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 76 publications
(169 reference statements)
1
1
0
Order By: Relevance
“…For high n or low µ, firms will rationally join a Windfall Clause even when their donation enmity is higher than their enmity (red line). about their capabilities, a result backed up by the literature on rivalry (Bar, 2006;Chen et al, 2017;Zucchini et al, 2019;Hutzschenreuter et al, 2021). In line with our above findings, if firms anticipate they will have public information rather than private or no information, then they believe that on average that the race is more dangerous.…”
Section: Firms Are More Likely To Join a Windfall Clause As The Compe...supporting
confidence: 79%
“…For high n or low µ, firms will rationally join a Windfall Clause even when their donation enmity is higher than their enmity (red line). about their capabilities, a result backed up by the literature on rivalry (Bar, 2006;Chen et al, 2017;Zucchini et al, 2019;Hutzschenreuter et al, 2021). In line with our above findings, if firms anticipate they will have public information rather than private or no information, then they believe that on average that the race is more dangerous.…”
Section: Firms Are More Likely To Join a Windfall Clause As The Compe...supporting
confidence: 79%
“…In relation to the topic of financing and investing in women-led businesses on factor 1 (strategic profits and entrepreneurial expectations) for subfactors (1-8) significant contributions have already been made by different researchers (He et al, 2022;Hutzschenreuter et al, 2021;Wan and Yiu, 2009;Yu et al, 2016), all of whom emphasise that the priorities of increasing efficiency in changes of prices, promotion and quality of products increase the profits of businesses. It is further suggested that strategic profit will increase when businesses know the identity of customers of their competitors and the business should be able to optimise productivity when information…”
Section: Discussionmentioning
confidence: 99%
“…We then compiled data at the "month × restaurant" level, ranging from October 2004 to December 2018. Hutzschenreuter et al (2021) noted that a firm's competitors affect its profitability; a restaurant's competition can therefore influence its survival. First, to measure the number of competitors per month for each restaurant, we calculated the dynamic restaurant competitor density in each month based on the number of restaurants in the same zip code using Zhang and Luo's (2018) method.…”
Section: Framework and Datamentioning
confidence: 99%